obstructive sleep apnea - kota, Shanthi Priya; Lavanya; Bandari, Gayathri; Ramesh Goud S.V; Chikurmally, Smriti (International Journal of Medical Research and Review, 2023)
The aim of this article is to provide a detailed description for obstructive sleep apnea regarding its signs and symptoms, the way it is diagnosed, the risk factors, management, the role of dentists and oral appliances in treatment. Obstructive sleep apnea (OSA) is a potentially life-threatening disorder characterized by repeated collapse of the upper airway during sleep, with periodic cessation of breathing for more than ten seconds. Dental professionals have a unique doctor patient relationship that can help them in recognizing the sleep disorder and co-managing the patients along with a physician or a sleep specialist. Oral appliance therapy is an important treatment modality for sleep apnea patients